THU0436 A Retrospective Non-Interventional Multi-Centre Study Evaluating Treatment Regimens Used in Psoriatic Arthritis Patients in Australia- The PSA Real Study. (15th July 2016) - Nicholls, D.; Nakayama, A.; Griffiths, H.; Littlejohn, G.; Bird, P.; Roberts, L.; de Jager, J.; Zochling, J.; Richter, S.; Louw, S.; Tymms, K.; ,
Abstract : Background: Psoriatic arthritis (PsA) is a spondyloarthritis spectrum disease with prominent involvement of skin and joints. The management of PsA patients is often complex and there is no uniformity across the medical profession. The majority of PsA studies have been prospective clinical trials involving a homogenous and restricted patient population. This may not reflect real clinical practice where patients have co-morbidities and other clinical characteristics that preclude them from participating in clinical trials. Objectives: To provide a cross sectional analysis of disease activity and management of PsA patients in the Australian population. Methods: This was a retrospective non-interventional multi-centre study using the Audit4 clinical audit program, with de-identified and routinely collected clinical data sourced from participating rheumatology practices in the OPAL consortium (Optimising Patient outcomes in Australian rheumatoLogy) across Australia during November 2015 1 . Data collected included baseline characteristics, prevalence and duration of cDMARD and bDMARD treatments, DAS28-CRP results, and reasons for stopping therapy. Results: A total of 3422 clinician diagnosed PsA patients were included in this study: 60% were female, mean age 54 years (±14) and mean disease duration 10 years (±9). Of patients with a valid treatment record (n=2948), 46% were on cDMARD monotherapy, 19% on bDMARD monotherapy, 13% on combination bDMARD and cDMARD therapy, 11% on combination cDMARD therapy and 10% were on no DMARDs. Of those with DAS28 CRP results (n=494), the highest mean DAS 28 CRP was 3.32 (±1.57) on combination cDMARD therapy, and the lowest DAS 28 CRP was 2.19 (±0.89) on bDMARD monotherapy. The most common reasons for cessation of cDMARD monotherapy was adverse reactions (41%), for bDMARD monotherapy lack of efficacy (26%) and combination bDMARD and cDMARD therapy either completed treatment or drug no longer required (37%). Conclusions: Cross sectional analysis of this large cohort managed in rheumatology clinical practice suggests most are receiving DMARD therapies with less disease activity on bDMARD monotherapy. Adverse reactions and lack of efficacy remain common reasons for cessation of cDMARD and bDMARD monotherapy in PsA. References: Tymms K, Littlejohn G. Optimising Patient Outcomes in Australian Rheumatology (OPAL): a clinician driven point of care observational data management consortium. Clin Exp Rheumatol 2014;32(85): S150-S152. Acknowledgement: Celgene Pty Ltd. Disclosure of Interest: None declared